Strategies, Tactics, and Techniques to Mitigate Against AI in Tertiary Education: Preserving Academic Integrity and Credibility - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V. (Integrated Journal for Research in Arts and Humanities, 2024)
The proliferation of artificial intelligence (AI) in tertiary education poses significant challenges to academic integrity and credibility. This study explores effective strategies, tactics, and techniques to mitigate these risks. Through a comprehensive literature review, analysis of current practices, and case studies, the research offers actionable recommendations for educators and policymakers. The findings highlight the importance of a multifaceted approach, combining technological solutions, pedagogical reforms, and ethical guidelines to uphold the standards of academic integrity in the face of AI advancements.